PENYULUHAN DAGUSIBU OBAT SEBAGAI UPAYA EDUCATION AND PUBLIC HEALTH PROMOTION MASYARAKAT DESA MULYOREJO KABUPATEN MALANG - Sella Paramitha; Mochammad Ramy Sundawa; Haris Maulana Yusuf; Ikhsan Maksum (Universitas Islam Malang, 2023)
With the advancement of technology and science, health problems related to drug use in Indonesian society are increasing. One of the factors is the lack of understanding among the public about the proper use of drugs. Therefore, the DAGUSIBU drug program is the right solution to address this problem. However, the village of Mulyorejo, Ngantang has never received any socialization about this program. The aim of this study is to increase public knowledge about how to obtain, use, store, and dispose of drugs rationally. This empowerment program was conducted using the method of preparation, counseling, which includes demonstration, interactive discussion, and evaluation through pre-test and post-test, as well as evaluation. The activities were carried out with enthusiasm and active participation from the participants. The socialization program went smoothly, with high enthusiasm from the participants. This can support the government's program in improving public health through the Gerakan Keluarga Sadar Obat (GKSO). In addition, the post-test results showed that the participants' knowledge of DAGUSIBU drugs significantly increased, enabling them to avoid mistakes in drug use. Through this socialization, the public can gain useful knowledge about proper drug use. This can be applied in daily life and provide benefits for the environment and family.